Cultural dimension of Indian family firms: Impact on Successor Selection - Jayantilal, Shital (2017)
India is one of the fastest growing economies and becoming a key player in the global business arena. The Indian economic landscape is dominated by family firms which range from small corner shops to global diversified conglomerates. A large majority of these firms are fast approaching the critical stage of succession. The way the challenge of executive succession is addressed is influenced by the cultural setting. The older generations are rooted in the traditional cultural norms whereas the younger generations are in closer contact with western values and more permeable to these. This paper uses a game theory approach to analyze the impact that culture has on successor selection in family firms, focusing on the younger generation’s cultural alignment with the underlining norms and values of the Indian society. The results emphasize that the younger generation’s cultural misalignment can jeopardize intergenerational succession and risk family harmony. The findings highlight the importance of promoting cultural congruence in the family firm.